EKSPRESI HIF-1α PADA KANKER OVARIUM EPITELIAL: PERDEDAAN ANTARA KASUS DENGAN ENDOMETRIOSIS DAN TANPA ENDOMETRIOSIS - Ramadhani, Rahmi; Asri, Aswiyanti; Tofrizal, Tofrizal; Yenita, Yenita; Agung, Puja; Yetti, Husna (Nusantara Hasana Journal, 2025)
Ovarian cancer is a cancer that grows in the ovaries where epithelial ovarian carcinoma is the most common type. Endometriosis is one of the risk factors for ovarian cancer. Understanding the microenvironment and mechanisms of endometriosis-related ovarian cancer carcinogenesis is needed to improve treatment and patient prognosis. Hypoxia is one of the microenvironments in endometriosis that can promote ovarian cancer through HIF-1α activation. HIF-1α activation can induce target genes involved in carcinogenesis and other intracellular signaling pathways. Research on HIF-1α with endometriosis-related ovarian cancer is still very limited and no one has compared it between groups with endometriosis and groups without endometriosis. This study aims to determine the differences in HIF-1α expression in epithelial ovarian cancer with endometriosis (EAOC) and without endometriosis (non-EAOC). The design of this observational analytical study with a cross-sectional design. The population of this study was all cases of epithelial ovarian cancer diagnosed in the Anatomic Pathology Laboratory of M. Djamil Padang Hospital from January 2024 to June 2025. A total of 34 cases of epithelial ovarian cancer were sampled, with a proportion of 17 EAOC cases and 17 non-EAOC cases taken by consecutive sampling. Slides that had been stained with hematoxyline and eosine (HE) were reevaluated for classification, type, grading, and staging. Paraffin blocks were collected for further HIF-1α immunohistochemistry (IHK) examination to analyze protein expression semiquantitatively (Immunoreactivity score). High HIF-1α expression was considered if the IRS score was 4-12. Statistical data analysis used the Chi-square test. Results: The results of the study found that the majority of EAOC patients were aged 41-50 years with an average age of 45 years, the most common parity status was multiparous, the most common type of endometriosis was endometriotic cyst (endometrioma), the most common histopathological type was type I, the most common histopathological grade was high grade, and the most common stage was early stage. There was no significant difference between HIF-1α expression in EAOC and non-EAOC (p = 1.000), as well as staging (p = 0.086). However, there was a significant relationship between HIF-1α expression and histopathological type (p = 0.034) and grading (p = 0.001) of epithelial ovarian cancer. High HIF-1α expression plays a greater role in the progression and aggressiveness of epithelial ovarian cancer, while its role in tumorigenesis and carcinogenesis still requires further research.